Intervensi Pekerja Sosial terhadap Penyandang Disabilitas Mental di Margo Laras Pati - Riyana, Desi; Kisworo, Bagus (Journal of Nonformal Education and Community Empowerment, 2019)
This study aims to describe the interventions carried out by social workers towards persons with disabilities in PSRSPDM Margo Laras Pati and its supporting and inhibiting factors. This research method uses a descriptive qualitative approach. Data is collected through observation, interviews, and documentation. Data validity techniques using source triangulation and technical triangulation. Data analysis techniques through data collection, reduction, data presentation, and conclusion/verification. It is generally concluded that the intervention of social workers towards persons with mental disabilities consists of five stages, namely: the initial approach stage, assessment, planning, implementation of interventions and evaluation. Supporting factors consist of motivation, environmental support, facilities, and infrastructure. While the inhibiting factor consists of the influence of the drug consumed, the lack of readiness of the beneficiaries and the existence of discriminatory actions.